PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA PT. GREENTECH KAWASAKI CAKRAWALA MOTORINDO DI KOTA PEKANBARU - Nafrial, Rizki Samzami; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the effect of product quality and brand imageon customer satisfaction. To analyze the effect of product quality and brand imageon Consumer loyalty. To analyze the effect of product quality on loyalty throughconsumer satisfaction. To analyze the influence of brand image on customerloyalty through satisfaction and to analyze the influence of customer satisfactionon consumer loyalty PT. Greentech Kawasaki Cakrawala Motorindo inPekanbaru City. Research population is consumer of PT. Greentech KawasakiCakrawala Motorindo in Pekanbaru City in 2017 as many as 575 consumers. Thesample size that will be used is 103 people. Data analysis using path analysismethod (path analisys). The results of this study indicate that Product Quality andBrand image influence on consumer satisfaction. Product Quality and Brandimage affect loyalty. This indicates that the better the brand image is positivecertainly increases loyalty. Product Quality significantly influence loyalty throughSatisfaction. Brand image influence satisfaction through loyalty. Satisfactionaffects loyalty.